Prevalence of Escherichia coli in a Swine Nursery Facility Pre- and Post-Disinfection - Macie E. Reeb; Kellen Habib; Jason C. Woodworth; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt; Sara E. Gragg (Kansas Agricultural Experiment Station Research Reports, 2022)
During the spring of 2021, the Kansas State University Swine Early Wean Facility (SEW) experienced a notable increase in piglet morbidity and mortality. Piglet diarrhea was observed approximately 2 to 3 weeks post-weaning along with an increase in number of sudden mortalities. Necropsy samples were collected and confirmed for clinical diagnosis ofEscherichia coliK88 infection by the Kansas State University Veterinary Diagnostic Laboratory.E. coliK88 can negatively impact performance of pigs and typically manifests as diarrhea, which can continue until death because of severe dehydration and metabolic acidosis or from terminal septicemia. Once present,E. coli, includingE. coliK88,tends to persist in the environment unless vigorous efforts are successful at sanitation and disinfection. Therefore, the overall objective of this study was to determine the critical areas in need of improved disinfection at the nursery facility and to make recommendations based on environmental sampling results. The research team surveyed the most probable areas of contamination before sampling and identified six locations from which to collect environmental samples in each pen. These six locations, in addition to other common-use areas in the barn, were sampled using sponges and swabs from 10 pens at random both pre- and post-disinfection. After the completion of sampling, samples were enumerated using Sorbitol MacConkey Agar with cefixime and tellurite (CT-SMAC).E. coliwas not detected from the common-use areas such as the water lines, office water faucets, and feed buckets. The dirtiest pen sample areas pre-disinfection included under rubber mats, inside and outside of waterers, and the floor slats. Disinfection significantly reduced (P<0.05) contamination of the floor slats and the waterer (inside and outside). While the slats were initially among the dirtiest samples, after cleaning, a 6.5 log reduction was observed. Conversely, contamination on the feeder surface and lip of the feeder was not significantly reduced post-disinfection (P>0.05).E. coliwas recovered from every sample type post-sanitation. While the current cleaning process was successful in reducing bacterial contamination, these data suggest it could be further improved by using a more effective and thorough cleaning process, as some residual contamination remained. Recommendations might include the use of a stronger disinfectant with power washing, higher water pressure, and increased water temperatures, among others. Perhaps physical scrubbing in hard-to-reach locations, such as rubber mats and water cups might also be helpful.
Keywords: E. coli; post-weaning diarrhea; disinfection procedures; nursery pigs